Improving User Experience and Conversion Rates in E Commerce through Content in an Industry-specific B2B Environment - Hurtíková, Adéla; Tahal, Radek, 1970-; Robert, Alexandre; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This thesis aims to establish an understanding of the importance of content on user interfaces for user experience and conversion rates on e-commerce websites. In order to showcase such importance on the one hand and uncover principles and procedures for successful UX writing in an industry-specific B2B environment on the other hand, a structured and user-centred approach and subsequent methods were utilized, including user and language observations, expert interviews and focus group, usability testing and quantitative A/B testing. This research explores whether the mere alteration of words on user interfaces can have positive effects on user experience and conversion rates. Further recommendations for improvement of user experience for the studied use case are presented alongside with the proposed setup for UX writing within the broader scope of digital product design and development in corporations.
Vedoucí práce: Radek Tahal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses